Diaryl Urea Derivative Molecule Inhibits Cariogenic Streptococcus mutans by Affecting Exopolysaccharide Synthesis, Stress Response, and Nitrogen Metabolism - Liao, Ying; Zhang, Mengyun; Lin, Xingnan; Yan, Fuhua (Frontiers in Cellular and Infection Microbiology, 2022)
Different small molecules have been developed to target cariogenic bacteria Streptococcus mutans. Based on target-based designing and in silico screening, a novel diaryl urea derivative, 1,3-bis[3,5-bis(trifluoromethyl)phenyl]urea (BPU), has previously been found effective in inhibiting the growth of S. mutans. However, the exact mechanism remains unclear. This current study aimed to explore the antimicrobial and antibiofilm effects of BPU on S. mutans and locate key enzymes and biological processes affected by the molecule via in silico molecular docking analysis and transcriptomic profile. Our in vitro results confirmed that BPU was capable of inhibiting planktonic growth as well as biofilm formation of S. mutans. The virtual binding analysis predicted that the molecule had strong binding potentials with vital enzymes (3AIC and 2ZID) involved in extracellular exopolysaccharide (EPS) synthesis. The predicted inhibitive binding was further confirmed by in vitro quantification of EPS, which found a decreased amount of EPS in the biofilms. The transcriptomic profile also found differential expression of genes involved in EPS synthesis. Moreover, the transcriptomic profile implied alterations in stress response and nitrogen metabolism in S. mutans treated with BPU. Examination of differentially expressed genes involved in these biological processes revealed that altered gene expression could contribute to impaired growth, biofilm formation, and competitiveness of S. mutans. In conclusion, the novel diaryl urea derivative BPU can inhibit the virulence of S. mutans by affecting different biological processes and serves as a potent anti-caries agent.